How increased stomatal density shapes root-shoot hydraulic coordination in Arabidopsis - Cáceres, Pablo D.; Manacorda, Carlos Augusto; Sutka, Moira; Asurmendi, Sebastian; Amodeo, Gabriela; Baroli, Irene (Sociedad Argentina de Fisiología Vegetal, 2025)
Poster